Growth of agro-industrial complex in modern economic conditions - Petrunenko, Iaroslav; V. Dukhnevych, Andrii; O. Kliutsa, Serhii; Karpinska, Nataliia; Demianyshyna, Olesia (Revista San Gregorio, 2020)
The long-term, stable development of the country, the standard of living of its population is primarily influenced by the ability of the state to fully meet the basic needs of the population, a prominent place among which is the nutritional requirement. At the same time, the level of meeting the population’s nutritional requirements is put into practice through the assessment of such a category as food security. Its sustainability to a great extent depends on the success of the development and functioning of the agro-industrial complex of the country, which is constantly affected by climatic factors, economic and financial, as well as political ones.